THE FIRST EXPERIENCE IN USING ADALIMUMAB IN PATIENTS WITH ANKYLOSING SPONDYLITIS: CLINICAL AND MRICOMPARISONS OF THE RESULTS OF THERAPY - A G Bochkova; O A Rumyantseva; T V Dubinina; A V Levshakova; O Yu Vakulenko; S O Krasnenko; Sh F Erdes; A G Bochkova; O Rumyantseva; T V Dubinina; A V Levshakova; O Yu Vakulenko; et al. (Научно-практическая ревматология, 2010)
Objective: To gain experience with adalimumab therapy in patients with ankylosing spondylitis (AS) and to clarify the effect of the drug on MRI-detectable inflammatory changes (IC) in the vertebral column and heel enthesis with the short-term use of this gene engineering biological. Subjects and methods. This open-label observation included 14 patients diagnosed as having AS in accordance with the modified New York criteria [4] and 3 patients with early undifferentiated spondyloarthritis (uSA). The ESSG criteria were used for the diagnosis of uSA. In addition to the BASDAI index, the new international index for disease activity in AS (ASDAS) proposed by the ASAS group in 2009 was first employed to assess the activity of AS. MRI-detectable IC in the thoracic spine, sacroiliac articulation, AND heel bones (in patients with heel enthesitis) was an additional criterion for AS activity. The results of adalimumab use were assessed at weeks 4 and 14 of the study. The efficiency of therapy was evaluated by the ASAS criteria, 40% improvement was taken into account, 50% improvement and partial remission were separately assessed; 50% improvement was assessed by the BASDAI index. The number of patients who had achieved partial remission after 6 adalimumab injections is the major efficiency criterion. Results. The median (Ме) age of all the patients was 31.6 years [range 22-56]; the Ме disease duration was 72 months [range 11-264]. HLA-B27 was detected in 83% of the patients. Peripheral arthritis and enthesitis were present in 12 and 9 patients, respectively. Partial remission was recorded in 17.8 and 41% of patients after 2- and 12-week adalimumab therapy, respectively; 40% ASAS improvement was observed in 58.8 and 76.6% of patients after 2- or more and 6-week therapy, respectively. The BASDAI activity index was decreased by 50% or more in 47 and 86.6% of the patients with the baseline high index after 2 and 6 injections, respectively. The ASDAS activity corresponded to low activity in 67 and 75% of the patients having the baseline high activity in this index (>3.0) after 2- and 12-week therapy, respectively. In 3 patients, 100% clinical improvement in heel enthuses was achieved, as confirmed by MRI data. Although the Ме IC in the thoracic spine substantially diminished from 8 (9) to 0 (1) following 12-week therapy, the differences were insignificant (p=0.07). After 12-week therapy, thoracic IC completely disappeared in one patient. Conclusion. Adalimumab therapy-induced improvement was frequently seen after just the first two injections of adalimumab and preserved after 12-week therapy. Adalimumab rapidly and considerably reduces the magnitude of inflammation in the spinal structures and entheses, as evidenced by МЫ data.